2010
DOI: 10.1007/s10333-010-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Rice root growth and physiological responses to SRI water management and implications for crop productivity

Abstract: This paper reports on several research findings on rice root responses, in terms of growth and physiology, manifested when applying System of Rice Intensification water management principles under semi-field and field conditions, in conjunction with variations in plant density and microbial density in the soil. The research aimed to learn about causal relationships, if any, between rice root and shoot growth at different growth stages of the rice plant's development and their cumulative effect on yield, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 28 publications
7
28
0
Order By: Relevance
“…There was a maximum amount of photosynthetic pigments present in Th-treated plants in maize and rice crops as compared to untreated plants under NaCl condition. Further, these results are in accordance with the results of Mishra and Salokhe (2011) who reported that inoculation of seed by Trichoderma enhanced pigment system PSII performance and produced a higher rate of transpiration in plants under salt stress conditions. In plants subjected to salinity stress, photosynthetic rate and stomatal conductance might be disturbed due to the higher amount of Na + ions accumulation which disturb the electron transport chain during photosynthesis (Kanwal et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…There was a maximum amount of photosynthetic pigments present in Th-treated plants in maize and rice crops as compared to untreated plants under NaCl condition. Further, these results are in accordance with the results of Mishra and Salokhe (2011) who reported that inoculation of seed by Trichoderma enhanced pigment system PSII performance and produced a higher rate of transpiration in plants under salt stress conditions. In plants subjected to salinity stress, photosynthetic rate and stomatal conductance might be disturbed due to the higher amount of Na + ions accumulation which disturb the electron transport chain during photosynthesis (Kanwal et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The trials reported by Mishra and Salokhe (2011) showed the importance of maintaining sufficient water available in the soil for plants during their reproductive phase. Some SRI practitioners, however, have reported good results from extending alternate wetting and drying (AWD) throughout the whole crop cycle (see also ).…”
Section: Areas For Further Research and Innovation In Sri Managementmentioning
confidence: 95%
“…An additional important benefit of aerobic soil conditions is the development of larger root systems, as reported by Barison and Uphoff (2011), Mishra and Salokhe (2011) and Thakur et al (2011). This gives rice plants larger exploitable root zones in the soil, which under anaerobic conditions are further restricted by the hard pan needed to hold water for maintaining flooding.…”
Section: Reducing Water Applicationsmentioning
confidence: 96%
“…Drought tolerance in mustard plants using Trichoderma is justified by the fact that enhanced rooting provides increased surface area for absorption and long roots penetrate deeper in soil which can absorb the deep seated water and increase plant stand in water stress conditions. In addition of biocontrol ability of Trichoderma spp., the activity that contributes to the enhancement of root growth and distribution was also considered as a key factor to the prolonged photosynthetic activity and the delayed senescence in rice plants (Mishra and Salokhe, 2011). Ghahfarokhy et al (2011) reported that colonization of roots with VAM fungi and Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%